Nonlinear Dependence (on Ionic Strength, Ph) of Surface Charge Density and Zeta Potential in Microchannel Electrokinetic Flow - Escudey-Castro, A; Escudey-Castro, A; Arancibia-Miranda, N; Arancibia-Miranda, N; Chen, D (Elsevier Ltd, 2023)
In this work, a numerical method is proposed to predict the electrokinetic phenomena and combined with an experimental study of the surface charge density (ρs) and zeta potential (ζ) behavior is investigated for borosilicate immersed in KCl and NaCl electrolytes, and for imogolite immersed in KCl, CaCl2, and MgCl2 electrolytes. Simulations and experiments of the electrokinetic flows with electrolyte solutions were performed to accurately determine the electric double layer (EDL), ζ, and ρs at various electrolyte concentrations and pH. The zeta potential was experimentally determined and numerically predicted by solving the coupled governing equations of mass, species, momentum, and electrical field iteratively. Our numerical prediction shows that ζ for borosilicate develops strong nonlinear behavior with the ion concentration following a power-law. Likewise, the ρs obeys a nonlinear behavior, decreasing as the concentration increases. Moreover, for imogolite, both ζ and the ρs behave nonlinearly with the pH. The EDL for borosilicate and imogolite becomes thinner as the electrolyte concentration and pH increase; this behavior is caused by increased ρs, resulting in the higher attraction of the free charges. The reported nonlinear behavior describes more accurately the interaction of the nanoparticle surface charge with the electrolytes and its effect on the electrolyte transport properties. © 2023 The Authors